If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1(-10) = x Multiply -1 * -10 3 + 10 = x Combine like terms: 3 + 10 = 13 13 = x Solving 13 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 13 + -1x = x + -1x Combine like terms: x + -1x = 0 13 + -1x = 0 Add '-13' to each side of the equation. 13 + -13 + -1x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -1x = 0 + -13 -1x = 0 + -13 Combine like terms: 0 + -13 = -13 -1x = -13 Divide each side by '-1'. x = 13 Simplifying x = 13
| 27x^2+72=0 | | 9x+5=4x+2+5x | | 24=x^2+2 | | f=52+1x | | -80*x=162 | | f(x)=49x+3x-1 | | 5x+4(2x-15)=57 | | (x^3)-(2*x*y^2)+(4*y)=8 | | 54=2n+3 | | (2x+15)+90+x=180 | | (x+9)=(4x-27) | | -16t^2+120t-0=0 | | -4x-5=-3 | | 2x+0.7=6x-0.8 | | ln(x^2+1)+ln(x^2-1)=0 | | 3x^2-5x^2-48x+80=0 | | 17+8(x-1)=-7 | | 19x+50=9(x+7) | | f(x)=3x^2-11x+28 | | 5y=-20x+10 | | Log[3]5-log[3]x=log[3]2 | | (2x+1)(x-3)(x-2)=0 | | ln(5x-9)=3 | | on(5x-9)=3 | | 16y^3-54=0 | | (x-5)(x^2-2x+7)= | | y^3-6y^2+11y=0 | | 12-6y=2y | | (4w+7)(5+w)=0 | | (6x-7)(6x+7)= | | 5+-= | | Log(3)5-log(3)x=log(3)2 |